COVID-19 : The Regulatory and Supervisory Implications for the Banking Sector: A Joint IMF-World Bank Staff Position Note. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This joint IMF-World Bank note provides a set of high-level recommendations that can guide national regulatory and supervisory responses to the COVID-19 pandemic and offers an overview of measures taken across jurisdictions to date.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet